Determinants of GDP Growth in Asean-5 Using Panel Method - Maria Anastasia Artvelia Perdana; Andryan Setyadharma (Ecoplan, 2022)
The spread of COVID-19 throughout the world has caused concerns around the world. This study’s aim is to assess the impact of COVID-19, especially on the economic sector. We examined the economic impact of the coronavirus in various ASEAN-5 countries by analyzing their respective economies from 2018 to 2020. The data was processed using the Panel Method. The results indicated that foreign exchange reserves and net exports have a negative and significant effect on the economic growth of ASEAN-5. While the exchange rate and stock price index have a positive and significant impact on the economic growth of ASEAN-5, it was found that FDI has no significant effect on the economic growth of ASEAN-5.